2008
DOI: 10.1002/hyp.7020
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐year water table recovery after clearcutting and draining boreal forested wetlands of eastern Canada

Abstract: Abstract:In boreal forested wetlands, the observed increase in the water table level after clearcutting (watering-up) is often a threat to sustained ecosystem productivity. Hydrologic recovery refers to the processes by which a water table progressively drops back to its initial level after the cut. In eastern Canada, drainage is used operationally after clearcutting wet sites in order to lower the water table level and accelerate hydrologic recovery. The objective of this study was to evaluate the duration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…A number of studies have documented similar responses across a range of climate and site types, with increases in WT height similar to those observed here (Bliss and Comerford 2002;Xu et al 2002;Marcotte et al 2008;Pothier et al 2003). Clear-cutting largely caused a delay in WT drawdown that was more pronounced in 2012 than 2013, and heights were higher than the control in both years, primarily when the WT was deeper than 30 cm.…”
Section: Harvest Treatment Effectssupporting
confidence: 73%
“…A number of studies have documented similar responses across a range of climate and site types, with increases in WT height similar to those observed here (Bliss and Comerford 2002;Xu et al 2002;Marcotte et al 2008;Pothier et al 2003). Clear-cutting largely caused a delay in WT drawdown that was more pronounced in 2012 than 2013, and heights were higher than the control in both years, primarily when the WT was deeper than 30 cm.…”
Section: Harvest Treatment Effectssupporting
confidence: 73%
“…These elevated water tables can persist for many years. Pothier et al (2003) did not detect water table recovery five years after harvesting, and Marcotte et al (2008) found that water table levels in undrained plots were still 5-7 cm higher than the pre-cut levels 10 years after clearcutting, which was attributed to precipitation interception by vegetation being only 50% of the pre-harvest value.…”
Section: Water Quantitymentioning
confidence: 93%
“…Extensive research that occurred during eras when demand for forest products from peatlands was high and from the European experience has identified many beneficial management practices to minimize impacts on water resources. Although peatland draining following clearcutting or precommercial harvesting helps in the recovery from watering-up, it is considered a costly and remedial approach to the problem (Marcotte et al 2008). For example, drainage should be limited to the first cohort stand following harvesting (Lavoie et al 2005) because the improvement in tree growth may be relatively small without additional fertilization (Jutras et al 2002).…”
Section: Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…However, watering up as a result of clearcutting (Heikurainen and Päivänen, 1970;Marcotte et al, 2008) may once again revive CH 4 production and emission from deep peat soils. One of the few studies relevant for our purposes examined the effects of clearcutting two nutrient-rich, drained peatland sites on CH 4 fluxes but found the changes to be negligible even though the WTL clearly rose, perhaps in part due to the slow re-establishment of methanogenic bacteria in old drainage areas (Huttunen et al, 2003).…”
Section: Introductionmentioning
confidence: 97%